2020
DOI: 10.3390/cancers12123854
|View full text |Cite
|
Sign up to set email alerts
|

The Role of cis- and trans-Acting RNA Regulatory Elements in Leukemia

Abstract: RNA molecules are a source of phenotypic diversity and an operating system that connects multiple genetic and metabolic processes in the cell. A dysregulated RNA network is a common feature of cancer. Aberrant expression of long non-coding RNA (lncRNA), micro RNA (miRNA), and circular RNA (circRNA) in tumors compared to their normal counterparts, as well as the recurrent mutations in functional regulatory cis-acting RNA motifs have emerged as biomarkers of disease development and progression, opening avenues f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 211 publications
(256 reference statements)
0
18
0
Order By: Relevance
“…As a type of non-coding RNA, LncRNA can regulate gene expression at multiple levels, including transcriptional and post-transcriptional regulation, translation, and post-translational modification, and thus affect a variety of biological functions, such as cell proliferation, differentiation, and apoptosis in cancer [ 10 ]. Among them, cis-acting is an important regulatory function of lncRNA, and its knockdown or overexpression will lead to changes in the expression of adjacent genes on the chromosome [ 11 ]. At present, relevant studies have shown that some lncRNAs are overexpressed, under-expressed, or even not expressed in AML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a type of non-coding RNA, LncRNA can regulate gene expression at multiple levels, including transcriptional and post-transcriptional regulation, translation, and post-translational modification, and thus affect a variety of biological functions, such as cell proliferation, differentiation, and apoptosis in cancer [ 10 ]. Among them, cis-acting is an important regulatory function of lncRNA, and its knockdown or overexpression will lead to changes in the expression of adjacent genes on the chromosome [ 11 ]. At present, relevant studies have shown that some lncRNAs are overexpressed, under-expressed, or even not expressed in AML.…”
Section: Introductionmentioning
confidence: 99%
“…At present, relevant studies have shown that some lncRNAs are overexpressed, under-expressed, or even not expressed in AML. Their abnormal expression will cis-regulate the expression of neighboring genes, and then play a role in promoting or suppressing cancer [ 11 , 12 ]. For example, Fernando et al found that a novel lncRNA CASC15 was up-regulated in acute lymphoblastic leukemia (B-ALL), and subsequently affected cell survival and proliferation by driving the expression of its adjacent gene SOX4 on the chromosome through the cis mechanism, thereby delaying the progression of acute leukemia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…DElncRNAs, which constituted 181 cis lncRNA-gene pairs. The cis-regulation function of non-coding RNA might participate in various biological processes (21) while the cis-regulation function of lncRNA might affect tumor progression (22,23). Our analysis indicated that DElncRNAs were mainly positive with adjacent protein-coding genes, with a negative correlation being relatively few in number.…”
Section: Discussionmentioning
confidence: 74%
“…It is well established that lncRNAs can exert regulatory effects on mRNAs ( Quinn and Chang, 2016 ; Tan-Wong et al, 2019 ; Elcheva and Spiegelman, 2020 ). The target genes of lncRNAs can be predicted on the basis of either their physical positions, in the case of antisense and cis- regulatory mechanisms, or their coexpression relationships, in the case of trans -regulation.…”
Section: Discussionmentioning
confidence: 99%